Test Procedures and Evaluation Tools for Passenger Vehicle Dynamics - Karlsson, Anders (My University, 2014)
Both within education and research it is necessary to be able to ensure that the real or virtual vehicle used, behaves as supposed. In order to verify this a massive set of test procedures is needed. However, to create a ruff overview showing the basic behaviour, some test procedures are implemented into an evaluation tool. The user of this tool is presented the results in a form of a report with numbers and diagrams Within this thesis a set of test procedures have been selected and implemented in an evaluation tool divided in to virtual test and analysis in order to both be able to use it for simulations as well as for post processing of real test data. This report focuses on the choice and implementation of a limited number of test procedures as well as the design of the evaluation tool developed. The tests that have been implemented are: Steady state cornering, Sine with dwell, Continuous sinusoidal input and Straight ahead acceleration. Other tests that were discussed and were suitable to be implemented at a later stage are: Step input, Random input, Sinusoidal input, one period, Pulse input, Braking with split coefficient of friction, Brake in turn and Straight braking. In order to give the user freedom to adjust the tests based on current requirements, all test procedure constants, e.g. times, velocities and distances, have been parametrized using an excel reference document to ensure good adaptability The tool developed within this test is easy to set up and supports batch processes which enables it to run several simulations using different models. This have been done with one model from the research project Balance Active and Passive Safety (BAPS). The evaluation tool is based on an combination of Matlab and Simulink. The results from the analysis part of the tool are presented as an pdf document. The purpose with creating this tool is to provide a method to easily and quickly get results on the behaviour of a real vehicle or a vehicle model during a few standard tests. This purpose is fulfilled with the tool created within this thesis.
Keywords: Farkostteknik; Transport; Vehicle Engineering; Transport